Development of a Web-Based Independent Curriculum Learning Assessment Application System for Raudhatul Athfal Teachers - Bakir, Widya Fitriani; Sukiman (Journal of Scientific Research, Education, and Technology (JSRET), 2024)
This study designs a web-based application model that is able to support the Merdeka Curriculum assessment effectively and efficiently and has obtained justification from experts and been tested on a limited scale. The method used is research and development (R&D) with the Borg and Gall model, which focuses on developing the Merdeka Curriculum learning assessment application for RA teachers. This research reached the preliminary field test stage to produce an application prototype, which still requires repeated testing on a wider scale. The results of validation by material experts show that this application is very feasible for use by RA teachers, with scores of 93.3% and 90%, respectively. Validation by media experts resulted in a score of 83.3%, indicating that the app is in the feasible category but requires some improvements. The field test showed that this application is very functional and easy to use by teachers for assessment management, with a user score of 95%. Based on these results, this study successfully developed and evaluated a web-based Merdeka Curriculum assessment application that is effective and in accordance with the needs of teachers in Raudhatul Athfal.